Focusing of transition radiation and diffraction radiation from concave targets; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 252, Iss. 1 - Potylitsyn A. P. Alexander Petrovich (2006, 2006)
In the article the transition radiation from a relativistic charge crossing a finite radius paraboloid target with taking into account the pre-wave zone effect is considered. It is shown that in this case the radiation cone narrowing occurs in contrast with the transition radiation from the flat target if the detector is situated at the distance, which is smaller than the focus distance (the focusing effect) from the target. At the charged particle passage through the central hole in a paraboloid target the diffraction radiation focusing (DR) occurs too. The focusing of coherent DR for the non-invasive measuring of the electron bunch length is proposed.